Further results on delay-dependent state feedback H∞ control of linear parameter varying time-delay systems - Shahbazzadeh, Majid; Sadati, Seyed Jalil (International journal of dynamics and control, 2022)
This paper is concerned with the H ∞ control problem for linear parameter varying time-delay systems subject to L 2 -norm bounded disturbances. Based on the Lyapunov-Krasovskii functional method, a new delay-dependent sufficient condition is derived for designing a state feedback H ∞ controller. In general, the coupling between decision variables and system matrices causes the results to be quite conservative. In order to obtain synthesis condition in terms of linear matrix inequalities, the well-known Young’s relation is employed to linearize the bilinear terms which unavoidably emerge in controller design for linear parameter varying time-delay systems. The proposed method can provide a controller with a larger delay range and a better disturbance attenuation effect. The efficiency and validity of the proposed control scheme are verified by the simulation results and comparisons.